2000
DOI: 10.1152/jappl.2000.89.3.1123
|View full text |Cite
|
Sign up to set email alerts
|

Impact of muscle injury and accompanying inflammatory response on thermoregulation during exercise in the heat

Abstract: This study examined whether muscle injury and the accompanying inflammatory responses alter thermoregulation during subsequent exercise-heat stress. Sixteen subjects performed 50 min of treadmill exercise (45-50% maximal O(2) consumption) in a hot room (40 degrees C, 20% relative humidity) before and at select times after eccentric upper body (UBE) and/or eccentric lower body (LBE) exercise. In experiment 1, eight subjects performed treadmill exercise before and 6, 25, and 30 h after UBE and then 6, 25, and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
(33 reference statements)
4
15
1
Order By: Relevance
“…The differences in oxygen and substrate utilization between trials indicate that factors other than exercise intensity may play a role in plasma IL-6 concentration. The findings from the current study agree with other studies that have shown a minor increase in plasma IL-6 concentrations with endurance exercise but no effect of temperature (Cosio-Lima, Desai, Schuler, Keck, & Scheeler, 2011;Lim et al, 2009;Montain, Latzka, & Sawka, 2000;Starkie et al, 2005). Although temperature did not influence plasma IL-6 levels, exercise elicited a significant increase in plasma IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…The differences in oxygen and substrate utilization between trials indicate that factors other than exercise intensity may play a role in plasma IL-6 concentration. The findings from the current study agree with other studies that have shown a minor increase in plasma IL-6 concentrations with endurance exercise but no effect of temperature (Cosio-Lima, Desai, Schuler, Keck, & Scheeler, 2011;Lim et al, 2009;Montain, Latzka, & Sawka, 2000;Starkie et al, 2005). Although temperature did not influence plasma IL-6 levels, exercise elicited a significant increase in plasma IL-6.…”
Section: Discussionsupporting
confidence: 90%
“…The final Tre on EIMD trial 2 was similar to the final Tre observed in the control group during HS on both CON trials (Fig 3b), although we acknowledge that these groups were composed of different individuals, so are not directly comparable. In our previous study (Fortes et al 2013), final Tre was 0.53 °C higher during HS following EIMD compared to control non-muscle damaging exercise in a repeated measures design, whilst Montain et al (2000), also demonstrated ~0.3 °C greater body temperature during HS following muscle damaging exercise compared to control exercise. It therefore appears that a prior bout of EIMD provides a significant degree of protection against the increased heat strain that EIMD elicits during subsequent exercise-heat-stress.…”
Section: Discussionmentioning
confidence: 70%
“…Non-heat-acclimated individuals undertaking heavy training bouts with an eccentric component in the heat are likely at increased risk of developing EHI (Fortes et al 2013;Montain et al 2000) e.g. athletes performing unaccustomed exercise, or soldiers running or walking across mountainous terrain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this effect has only been evidenced from higher exercising T core during exercise performed many hours after the damaging stimulus (6,34) and may depend on prior migration of activating agents such as neutrophils, macrophages, and PAF (41, 51). The exercise undertaken in this study was not performed to exhaustion, and none of the subjects reported difficulty or injury as a consequence of the exercise schedules.…”
Section: Discussionmentioning
confidence: 99%